A Vigilance Explanation of Musical Chills? Effects of Loudness and Brightness Manipulations. (8th April 2020) - Bannister, Scott
Recent research has suggested that low-level psychoacoustic parameters such as loudness and spectral brightness are correlated with musical chills, a subjective emotional experience accompanied by goosebumps, shivers, and tingling sensations. These relationships may be explained by a vigilance theory of chills, through the process of auditory looming; however, these correlations or theories have never been causally tested. In the current study, participants ( N = 40) listened to five variations (original, low loudness, high loudness, low brightness, high brightness) of an experimental and control piece of chills music, characterized by a crescendo and guitar solo respectively; this qualitative distinction was made based on whether the underlying musical structure of the pieces was or was not capable of engaging auditory looming processes. It was predicted that increases in loudness would result in increased chills frequency across participants, indicated by button presses; brightness was included as an exploratory parameter. Results show that for the experimental piece, increases in loudness resulted in significantly more frequent chills experiences, and increases in brightness significantly reduced the frequency of chills, whereas no effects were found for the control piece. Findings are discussed in terms of vigilance and social bonding theories of chills, and the complex interactions between low-level psychoacoustic properties and higher-level musical structures.